Nicaragua : Seventh Review Under the Extended Credit Facility and Financing Assurances Review: Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Nicaragua. (IMF Staff Country Reports; Country Report ;, 2011)
The Nicaraguan economy continued to post robust growth in the first half of 2011. The Seventh Review Under the Extended Credit Facility (ECF) and Financing Assurances Review highlights that all quantitative performance criteria for end-June 2011 were met and the structural agenda is broadly on track. The fiscal performance of the central government was stronger than envisaged. The deficit in the external current account is projected to remain large and to be financed by resilient capital flows.